(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
Over the last decade there has been a growing emphasis on utilizing social protection as a policy framework to tackle poverty and vulnerability in developing nations. An increasing multitudeof governments in developing nations are formulating and embracing comprehensive national social protection strategies as part of their initiatives to alleviate poverty. The implementation of social protection policies and programs in developing nations is rapidly expanding both in quantity and coverage, marking a significant increase in their reach and impact. From a qualitative standpoint, this study emphasizes the critical role of public spaces in alleviating poverty-related feelings in Vision 2030 and social housing at the scale of urban form. Flourishing individuals is one of the domains of community well-being (VanderWeele, 2019).